Transcatheter pulmonary valve implantation with custom-made 35-mm Myval™ transcatheter heart valve - Sivasubramanian Ramakrishnan; Nabeel Valappil Faisal; Lamk Kadiyani; Saurabh Kumar Gupta; Muthukumaran Chinnasamy Sivaprakasam (Annals of Pediatric Cardiology)
Transcatheter pulmonary valve implantation (TPVI) is the standard of care in patients with repaired tetralogy of Fallot (rTOF) presenting with right ventricular outflow tract (RVOT) dysfunction. However, the feasibility of TPVI is limited by the high cost and nonavailability of larger-sized valves for dilated native RVOT of rTOF patients. We report the first successful TPVI with a custom-made 35 mm balloon-expandable valve (Myval™) in a 30-year-old rTOF patient with severe pulmonary regurgitation and RV dysfunction.